(untitled) (Research, Society and Development, 2021)
The new coronavirus, SARS-CoV-2, which causes COVID-19 is easily transmitted from person to person. About 15% develop severe pneumonia and of these, 6% progress to severe acute respiratory syndrome (SARS) and multiple organ failure. Identify biomarkers that can predict which individuals are likely to be affected by severe disease and are at risk of death is crucial. However, the pathophysiology of the disease is not completely elucidated and the characterization of the clinical profile of people infected with SARS-CoV-2 remains unclear. Therefore, the objective of this study was to evaluate the epidemiological and laboratory profile of patients confirmed with COVID-19 and admitted to the University Hospital Lauro Wanderley, based on the correlation of laboratory tests to the evolution of the disease, determination of the most influential variables in the worsening of the disease. Data consisted of complete blood count and serum biochemical analyzes. Overall, 74 patients met all criteria of this study and were included, 40 from the Intensive Care Unit (ICU), and 34 from the Infectious Diseases Infirmary (IDP), both exclusively for patients with COVID-19. Based on these findings, patients with increased WBC count, ALT, AST, and LDH should be closely monitored as these factors predict ICU admission and mortality. Among other laboratory parameters, patients admitted to the ICU have higher levels of D-dimer compared to IDI patients. The results suggests that higher levels of D-dimer on admission is related to a worse prognosis of the disease.